2014
DOI: 10.1371/journal.pone.0101165
|View full text |Cite
|
Sign up to set email alerts
|

Gaussian Mixture Modeling of Hemispheric Lateralization for Language in a Large Sample of Healthy Individuals Balanced for Handedness

Abstract: Hemispheric lateralization for language production and its relationships with manual preference and manual preference strength were studied in a sample of 297 subjects, including 153 left-handers (LH). A hemispheric functional lateralization index (HFLI) for language was derived from fMRI acquired during a covert sentence generation task as compared with a covert word list recitation. The multimodal HFLI distribution was optimally modeled using a mixture of 3 and 4 Gaussian functions in right-handers (RH) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
304
10
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 296 publications
(341 citation statements)
references
References 34 publications
26
304
10
1
Order By: Relevance
“…Although it is generally assumed that language lateralization was predictive of hand preference (Knecht 2000), recent findings have questioned this relationship when disregarding subjects who are strongly right language lateralized (Mazoyer et al 2014). Although our study was not specifically aimed at Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is generally assumed that language lateralization was predictive of hand preference (Knecht 2000), recent findings have questioned this relationship when disregarding subjects who are strongly right language lateralized (Mazoyer et al 2014). Although our study was not specifically aimed at Fig.…”
Section: Discussionmentioning
confidence: 99%
“…One prominently lateralized functional network underlies the human ability to speak and understand language, and critically involves the Superior Temporal Gyrus (STG) and the auditory cortex of Heschl's Gyrus (HG), both of which show anatomical asymmetry (Agcaoglu, Miller, Mayer, Hugdahl, & Calhoun, 2014;Dikker, Silbert, Hasson, & Zevin, 2014;Lyttelton et al, 2009;Mazoyer et al, 2014;Menenti, Gierhan, Segaert, & Hagoort, 2011;Willems, Van der Haegen, Fisher, & Francks, 2014). These regions have also shown microanatomical (Hutsler, 2003) and neurophysiological (Morillon et al, 2010) lateralization; left-sided neural oscillatory frequencies reportedly correspond to syllabic speech rhythms (Morillon et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…High mean LIs of between 0.74 and 0.89 have been reported for sentence generation, both when sentences are pre-learnt prior to scanning (e.g., Stippich et al, 2003), and when they are actively generated during the scan (e.g., Tzourio- Mazoyer et al, 2016). However, other studies have reported more modest laterality estimates of between 0.48 and 0.65, again with both variants of the task (Mazoyer et al, 2014;Partovi et al, 2012a;Partovi et al, 2012b). Thus, it does not appear to be the case that strength of laterality differs according to whether sentences are generated spontaneously during the scanning session, or learnt prior to scanning.…”
Section: Strength Reliability and Robustnessmentioning
confidence: 81%